The varying social dynamics in orally transmitted and notated vs. improvised musical performance - Hadar, Tamar; Rabinowitch, Tal-Chen (Frontiers in Psychology, 2023)
Musical performance can be viewed as an intricate form of social behavior. Accordingly, the rich diversity of existing musical styles and traditions may reflect distinct modes of social interaction. To gain a better understanding of the relations between musical style and social dynamics, we have formulated a framework for dissecting different genres of musical performance according to key social criteria. In particular, we contemplate on the continuum ranging from strictly orally transmitted and notated to fully improvised music, and its relation to general compliance with social norms and structure, borrowing key concepts from tight-loose theory, a powerful paradigm for studying societal behaviors and tendencies. We apply this approach to analyze four distinct prominent musical genres, providing a detailed mapping between musical style and social dynamics. This work highlights important factors that link between musical performance and social interaction, and will enable future experimental unraveling of social aspects of musical performance as expressed by different musical styles and practices.